High reliability of tests of maximum throwing performance - Harasin, D.; Dizdar, D.; Markovic, G. (Journal of Human Movement Studies, 2006)
The objective of this study was to evaluate the reliability of maximum ball/medicine ball speed in three throwing tests. Seventy-seven physical education students were tested on maximum throwing performance by means of a Doppler radar gun. The tests of interest were seated one-arm handball throw, seated one-arm medicine ball throw, and seated medicine ball ehest throw. There was no systematic bias in the tested performances among the consecutive throwing trials of each test. The limits of agreement for maximum ball speed in all three tests ranged from 0.1 ± 0.4 m/s to 0.3 ± 0.8 m/s, suggesting that in 95% of repeated trials the projectile speed might be from 0.5 m/s less to 1.1 m/s greater than the original estimate. The coefficients of Variation for all tests were between 2.0% and 2.2% (95% confidence intervals; 1.7-2.6%) suggesting a low within-individual variability. The intraclass correlation coefficients ranged between 0.97 and 0.98 (95% confidence intervals 0.96-0.99).